ESTIMATION OF PLASMA VOLUME IN PATIENTS PRESENTING WITH ACUTE DECOMPENSATED HEART FAILURE USING KAPLAN – HAKIM FORMULA AND CORRELATION OF PLASMA VOLUME SHIFT WITH OUTCOMES - Das, Dipak Ranjan; DAS, BISWAJIT; SINGH, ANIL KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Simple and non-invasive methods are required to estimate the plasma volume expansion to assess the congestion status in heart failure patients. To determine the effectiveness of Kaplan–Hakim formula in the quantification of the plasma volume expansion in acute decompensated heart failure (ADHF) and the correlation of the outcome factors with plasma volume shift (PVS). Methods: This prospective study included 384 participants diagnosed with ADHF. Newly diagnosed cases and patients receiving treatment for the past 6 months were included. Kaplan–Hakim formula was used to estimate the plasma volume. Duration of hospital stay, subsequent hospitalization for heart failure (HHF), cardiovascular disease mortality, and all-cause mortality rate at the end of follow-up time was also noted. Results: Among the study participants, 88 patients (22.92%) had PVS <5%, while the remaining 88.5% of the patients had PVS more than or equal to 5%. A strong association between guideline-recommended dose of ACEi/ARBs, beta-blockers, and normalcy of plasma volume status (p<0.001) was found. The mean duration of stay, number of repeated hospitalization, the incidence of worsening renal function, CV mortality rate, and all-cause mortality rate were significantly lower in participants with PVS ≥5% in comparison to those who had PVS < 5%. Kaplan–Hakim formula is a more practical and easy way to measure volume status in patients with ADHF. Conclusion: The use of RAAS antagonists and beta-blockers in their optimal dosage is associated with favorable plasma volume status in chronic HF patients.